Human Emotions in Behavioral Sciences and Management Practices (UNWE Yearbook, 2014)
Organizational effectiveness, both overall and economic, is largely determined by the quality of management of the most important resource it employs, the Human Resource. While this is a universal truth, it becomes even an apparent truth in the context of modern societies and knowledge-based economies. There is a series of neuroscience achievements in the understanding of human emotionality, which are sinking in unnaturally slowly in the thinking of psychologists, and even more slowly and more unobtrusively in the interests and work of specialists in I/O Psychology, OB and economists. These fields (hence, people management practices) still host paradigms and attitudes typical of old times, whilst the concept of the organizational world and the human inside it continues to be unnaturally schematized, often enough, bluntly wrongly so.